From fans to protest: K-Poppers fangirl in digital movement in Indonesia - Mulyana, Tiara Alya; Wahyuningroem, Sri Lestari (Universitas Islam Negeri Ar-Raniry, 2025)
K-Poppers were one of the groups that were present when protests regarding the Omnibus Law surfaced in 2020, especially on social media such as Twitter. K-Pop fans, otherwise known as fandom, raised the #TolakOmnibusLaw movement on social media platforms including Twitter. This study specifically discusses fangirls, or female fan groups, who dominate K-Poppers accounts in Indonesia and their activism in voicing and supporting #TolakOmnibusLaw. Fangirls are often stigmatized by society and the mass media as irrational, hysterical, and lacking the capacity to understand issues in society. This study used a sequential mixed-method strategy with two data collection methods to obtain the desired findings. Quantitative data collection using data crawling and Social Network Analysis (SNA) was necessary to identify K-Pop accounts that participated in digital activism on Twitter during the 2020 Omnibus Law protests. Subsequently, qualitative data were gathered through in-depth interviews conducted online and offline to analyze the trends of digital activism displayed by K-Pop accounts on Twitter in rejecting the Omnibus Law. Through this study, which is part of the research related to K-Poppers' digital activism in the #TolakOmnibusLaw action, we argue that the stereotype against fangirls is not proven. Through their fangirling accounts, they strategize to build awareness and solidarity among K-Pop fans and the wider public against the process and substance of the Omnibus Law that harms labor groups and other aspects of society. Their activism is based on their closeness to their conditions as workers and students who will also become workers in Indonesia.